The Impact of R&D Tax Incentives on R&D Costs and Income Tax Burden - Christina Elschner; Christof Ernst (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
We analyse R&D tax incentives in a detailed way considering a multi-period setting and economic assumptions which reflect a realistic economic environment. We measure the incentive's impact on the firm's total tax payments and the R&D cost by means of the simulation model European Tax Analyzer. Using different economic settings and model firms, we run sensitivity analyses and get by that a more detailed view on the effects from R&D tax incentives against the background of the framing tax system. We find that not so much the kind but rather the specific design of R&D tax incentives, the interplay with the framing tax system and the firm's profitability relative to the level of R&D expenditures heavily influence the amount of tax subsidy for R&D.
Keywords: O38; H25; O31; 330; R&D; Tax incentives; Corporate Tax Burden; EU; Forschungssubvention; Industrielle Forschung; Steuerbegünstigung; Forschungskosten; Körperschaftsteuer; Steuerbelastung; Steuerwirkung; Vergleich; EU-Staaten